Passivbilden Bahasa Jerman - Burhanuddin (South Sulawesi Education Development, 2025)
This study aims to provide a comprehensive overview of students' abilities in constructing passive sentences in German. The research employs a descriptive method with a quantitative approach, using a single variable: the ability to construct passive sentences. Data were collected through written tests consisting of Richtig oder Falsch, Ordnen die Wörter im Passiv, and Formulieren die Sätze im Passiv. The technique used for data analysis is the percentage technique. The research population comprises 40 students from the German Language Education Study Program, with a sample of 20 students. The results show that the students' ability in the Richtig oder Falsch test is 61.5%. The students' ability in the Ordnen die Wörter im Passiv test is 77.5%. The students' ability in the Formulieren die Sätze im Passiv test is 30%. Based on data analysis, it was found that the students' ability to construct passive sentences in Präsens, Präteritum, and Perfekt forms is categorized as low (50.55%).